2009
DOI: 10.1210/me.2008-0198
|View full text |Cite
|
Sign up to set email alerts
|

Significance and Mechanism of CYP7a1 Gene Regulation during the Acute Phase of Liver Regeneration

Abstract: Cholesterol 7alpha-hydroxylase (CYP7a1) is the rate-limiting enzyme in the classic pathway of bile acid synthesis. Expression of CYP7a1 is regulated by a negative feedback pathway of bile acid signaling. Previous studies have suggested that bile acid signaling is also required for normal liver regeneration, and CYP7a1 expression is strongly repressed after 70% partial hepatectomy (PH). Both the effect of CYP7a1 suppression on liver regrowth and the mechanism by which 70% PH suppresses CYP7a1 expression are unk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
70
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 74 publications
(76 citation statements)
references
References 37 publications
5
70
0
1
Order By: Relevance
“…Cyp7a1 levels must rapidly decrease post PH, otherwise bile acids accumulate and cause hepatocyte apoptosis. 48 Paralleling DPB, Cyp7a1 mRNA levels were higher in HET livers pre-and post PH (Supplementary Figure 6), confirming higher levels of a functional DBP protein in HET livers. DBP also influences lipid metabolism by inducing insulin-like growth factor binding protein 1 (IGFBP1), which downregulates INSIG2, an inhibitor of de novo lipogenesis.…”
Section: Discussionmentioning
confidence: 68%
“…Cyp7a1 levels must rapidly decrease post PH, otherwise bile acids accumulate and cause hepatocyte apoptosis. 48 Paralleling DPB, Cyp7a1 mRNA levels were higher in HET livers pre-and post PH (Supplementary Figure 6), confirming higher levels of a functional DBP protein in HET livers. DBP also influences lipid metabolism by inducing insulin-like growth factor binding protein 1 (IGFBP1), which downregulates INSIG2, an inhibitor of de novo lipogenesis.…”
Section: Discussionmentioning
confidence: 68%
“…While diet containing 0.2 % cholic acid is stimulatory, feeding of a 1.0 % cholic acid diet resulted in mortality in hepatectomized mice indicating that toxic bile salt levels had been reached [40]. PHx in mice is accompanied by decreased basolateral uptake and synthesis of bile salts, while bile salt secretion is increased [41].…”
Section: Bile Salts and Liver Regenerationmentioning
confidence: 99%
“…PHx in mice is accompanied by decreased basolateral uptake and synthesis of bile salts, while bile salt secretion is increased [41]. Fxr-dependent downregulation of Cyp7a1 accounts for decreased bile salt synthesis in mice after PHx [40]. When Cyp7a1 is not suppressed due to genetic Fxr deficiency or transgenic overexpression of CYP7A1, liver regeneration is impaired by outbalanced apoptosis and decreased DNA synthesis resulting in reduced post-PHx survival [40].…”
Section: Bile Salts and Liver Regenerationmentioning
confidence: 99%
See 1 more Smart Citation
“…Huang et al found that FXR-dependent BA signaling was required for [9] . In response to the increased BA flux after 70% PH, FXR activates hepatic SHP and intestinal FGF15, which results in the suppression of Cyp7A1 and BA synthesis [9,61,62] . Another FXR target gene, the bile salt export pump (BSEP), a canalicular BA effluxer [63] , can also be induced to enhance BA export [9] .…”
Section: Fxr Liver Regeneration/repair and Liver Cancermentioning
confidence: 99%